Linguistic and semiotic representation of pessimism in The Happy Prince and Other Tales by Oscar Wilde - Volkova, Svitlana; Boichuk, Valentina; Pavliuk, Alla; Yefremova, Nataliia (East European Journal of Psycholinguistics, 2023)
This paper focuses on the indirect means of verbalising the phenomenon of pessimism in the texts of literary fairy tales from the point of view of linguosemiotics. The study aims to identify the linguistic and semiotic means that create the pessimistic discourse of Oscar Wilde's collection The Happy Prince and Other Tales. Pessimistic discourse is treated as a person-centred type of discourse, represented by a complex system of means that reveals the speaker's pessimistic worldview and is characterised by its aims, style, and tenor. The study employs semantic and lingo-semiotic analysis of the ontological phenomenon of pessimism in fictional texts, using content analysis to ensure the reliability and validity of the results. Furthermore, the four-stage methodological procedure used in this research allows us to define a general literary context of the analysed works, select the research material, determine the frequency characteristics of the symbols as lingo-semiotic means that create the pessimistic tonality and discourse of Oscar Wilde's collection The Happy Prince and Other Tales. The research identifies the symbols of nature (seasons, flowers), the material world (colours, everyday objects), distance and death (as an ontological category) as verbal triggers of the author's pessimism implemented in the narrative through the contextual markers of basic, adjacent and related qualitative features of pessimism reflecting its social, psychological and cognitive aspects. The study contributes to the development of linguistic semiotics, psycholinguistics and discourse studies by enriching the knowledge of idiostyles. The proposed methodology of the given research is considered promising within the framework of different genres. Disclosure StatementNo potential conflict of interest was reported by the authors.* Corresponding author: Alla Pavliuk, 0000-0002-6037-4819 allapavliuk@vnu.edu.ua